Pengaruh Return On Asset (ROA), Return On Equity (ROE) Dan Earning Per Share (EPS) Terhadap Harga Saham Pada Perusahaan Makanan Dan Minuman Yang Terdaftar di Bursa Efek Indonesia - Thaariq, Jiddan Ath; Padikromo, Suparno (Peneliti.net, 2024)
This study aims to explore, analyze, and provide a description of the effect of Return On Assets, Return On Equity, and Earning Per Share on Stock Prices in food and beverage sub-sector companies listed on the IDX in the 2018-2022 period. The research method used is descriptive quantitative. The sampling technique used was purposive sampling, and there were 17 out of a total population of 89 companies with a total of 85 data. The data used is secondary data obtained from the Indonesian Stock Exchange website. Analysis was performed using descriptive statistics, classical assumption test, multiple linear analysis, and hypothesis testing. The results of this study indicate that partially, Return On Assets (ROA) and Return On Equity (ROE) have no effect on stock prices, while Earning Per Share (EPS) has an influence on stock prices. In addition, these three variables, namely Return On Assets, Return On Equity and Earning Per Share together also have an influence on stock prices.